Training Levies : Evidence from Evalualtions - Dar, Amit (World Bank, Washington, DC, 2012)
This note examines one of the most commonly used techniques for generating resources from employers - payroll levies. In many countries payroll taxes on enterprises (with reimbursement for training undertaken) have become a significant source of financing for skills training, both in specialized training institutions and in enterprises.